Acute Central Toxic Keratopathy Induced by Exposure to Chinese Herbal Medicine Fluid for Verruca Plana: A Case Report - Shuang Zhang; Yong Tao (Case Reports in Ophthalmological Medicine, 2025)
Conclusion: Acute central toxic keratopathy could occur after exposure to Chinese herbal medicine fluid, and enhanced topical steroid treatment worked well for alleviating inflammation and reducing corneal opacity.